Pengaruh Penggunaan Foodstagram Endorsement Terhadap Buying Interest Pada Followers Instagram Kuliner Solo - Ilham Karin Rizkiawan; Aulia Uswatun; Latifah Putranti; Doni Hermansyah (Universitas PGRI Yogyakarta, 2023)
Instagram is widely used by social media users. The level of trust of Instagram followers especially in the culinary sector is very dependent on recommendations from the accounts they followed, so many business people endorse Instagram accounts that have many followers to promote their culinary businesses. This study aims to determine the effect of the dimensions of visibility, credibility, attractiveness,and strength on the buying interest of followers of culinary Instagram accounts in the city of Solo.This research includes quantitative research with a survey approach. The sample in this study was 150 culinary followers in the city of Solo and the sampling technique used was the purposeful Sampling method. The technique for analyzing data in research used reliability testing, validity testing, and multiple linear regression. The results of the study showed that the visibility variable had no significant positive effect on buying interest, while the variables of credibility,attractiveness,strength have a significant positive effect on buying interest.The suggestion in this research is that the culinary foodstagram account admin needs to pay attention to credibility when providing honest and appropriate reviews so that potential consumers do not feel disappointed if what is displayed in the content does not match what is reviewed